A Homogeneous Label-Free Electrochemical microRNA Biosensor Coupling With G-Triplex/Methylene Blue Complex and λ-Exonuclease-Assisted Recycling Amplification - Meng, Yao; Chen, Fangming; Jiang, Mingrui; Guo, Qin; Wang, Yaqiong; Wang, Jian; Zhang, De-Wen (Frontiers in Chemistry, 2021)
A novel homogeneous label-free electrochemical biosensor using G-triplex/methylene blue (G3/MB) complex as the signal generator together with an amplification assisted by the λ-exonuclease (λ-Exo) has been successfully constructed for ultrasensitive microRNA (miRNA) detection. An integrated microelectrode was designed to realize the miniaturization of the homogeneous electrochemical assay. Taking advantage of G3, that can specifically bind with MB and decrease its diffusion current, a single-stranded functional DNA hairpin structure was designed as the bio-recognition probe. The probe consisted of G3, eight bases to block G3, and the complementary sequences of the target miRNA. Here we chose miRNA141 - a potentially diagnostic biomarker of prostate cancer as the model target. The presence of miRNA141 could hybridize with the probe DNA to form a double-stranded structure with a 5’-phosphorylated terminus. Then λ-Exo was adopted to digest mononucleotides from the 5’-end, leading to the release of G3 part and miRNA141. The released miRNA could hybridize with another probe to trigger the cycling process, while the released G3 could therefore interact with MB to cause a detectable decrease of diffusion current. The proposed strategy showed a low detection limit of 16 fM and an excellent specificity to discriminate single-base mismatches. Furthermore, this sensor was applied to detect miRNA141 from diluted human serum samples, indicating that it has great potential in the application of nucleic acid detection in real samples.